Correlation of Knowledge, Nutritional Status, and Physical Activity with Incidents of Dysmenorrhea on Female Students of YLPI Pekanbaru tahun 2018: Hubungan Pengetahuan, Status Gizi dan Aktivitas Fisik dengan Kejadian Dismenorea pada Siswi SMA YLPI Pekanbaru tahun 2018 - Rika Karmila; Winda Septiani (Jurnal Kesehatan Komunitas, 2019)
Dysmenorrhoea is pain when menstruation is felt in the lower part of the abdomen that comes from cramps in uterus. Dysmenorrhoea is divided into primary dysmenorrhoea and secondary dysmenorrhoea Based on early survey, that always there are students going to UKS every month and permission not to attend the learning process because they have dysmenorrhea, and most of the students prefer to go home because of unbearable pain. Based on interviews, from 15 female students, 26.67% of them have never experienced dysmenorrhoea. 73.77% said they had different menstrual pain complaints.This researchh purpose is to knowing correlation of nutrition status , physic activity, and knowledge toward incidents of dysmenorrhea on female students of YLPI Pekanbaru senior high school in 2018. This research type is qualitative analytic with cross sectional design. The sample in this reseach were XI and XII grade, totaling 143 peoples. Data collection was conducted by distributing questionnaires for variables of dysmenorrhea, physical activity and knowledge. Measuring height and weighing female students was conducted for nutritional status variables. The research result show that, there are meaningful correlation among nutritional status (Pvalue= 0,016) andPR (95% CI)= 5,600 (1,449-21,641), physical activity (P value = 0,003) andPR (95% CI)= 6,587 (2,000-21,695), knowledge (P value = 0,004)andPR (95% CI)= 6,000 (1,887-18,083) with incidents of dysmenorrhea on female students of YLPI Pekanbaru Senior High School in 2018.Suggestions for the school to form Youth Counseling Information Center in environment of YLPI Senior High School that is useful as a forum for giving or educating information such as adolescent health, especially regarding dysmenorrhoea